Lithostratigraphy of a long, fossiliferous Oligocene sequence: Revisiting Saint Jacques, Nei Mongol, China - Wang, Bian; Zhang, Zhao-Qun; Wang, Yuan-Qing; Li, Qian; Bai, Bin; Liu, Yan; Mao, Fang-Yuan; Wang, Hai-Bing; Wang, Jian; Gong, Yan-Xin; Dong, Li-Ping; Wang, Li-Hua; et al. (Frontiers in Earth Science, 2023)
For a hundred years the Saint Jacques area has been known to produce rich Oligocene vertebrate fossils, yet only a handful of previous studies have focused on this area. Since 2010, we have conducted 12 field expeditions to Saint Jacques, and here we report findings from our paleontological excavations and stratigraphical investigations. Twenty-two fossiliferous blocks across the area are recognized and a chronostratigraphic framework has been established to aid fossil collection. Fossil-mammal materials have been recovered in situ from 1635 localities and additionally from surface sediments. Fossiliferous blocks in the area are correlated by lithological similarity and lateral tracing. Lithologically, the area is mainly composed of reddish silty mudstone and muddy siltstone, with three distinctive layers of grayish white sandstone. The measured composite stratigraphic column spans 239 meters and are divided into 12 lithostratigraphic units. Contrary to previous knowledge that Saint Jacques contains two Oligocene mammalian assemblages, our preliminary biostratigraphic analysis of small mammals shows that the area documents successive faunal transition from the Eocene to possibly the early Miocene. The hyracodontid perissodactyl Ardynia, the ctenodactyloid rodent Gobiomys, and the basal Glires Gomphos from the bottom litho-units imply the presence of the Eocene–Oligocene boundary, while small mammal assemblage of the top units is similar to Miocene faunas in northern China and Mongolia. Thus, rock strata in Saint Jacques likely span the Eocene through the early Miocene, bracketing an entire Oligocene sequence within. In sum, our re-exploration of Saint Jacques has greatly expanded the chronostratigraphic and taxonomic coverage of the mammalian fossil collection from this area. This long, successive Oligocene sequence makes an important record for studying the Eocene–Oligocene Transition. Further study in this area will contribute to a range of paleontological and paleoenvironmental questions.